Haematological Changes in Stored Blood - Karama M. I. Al Nuaimy (College of Education for Pure Sciences, 2008)
Abstract Blood transfusion is the process of referring blood. Or blood - based products from one person into the circulatory system of another blood transfusion may treat medical condition. The blood bank is the section of the lab that processes and distributes blood products under the supervision of a medical director certified in transfusion medicine. This study was conducted to determine the effect of storage for varying periods on some haematological parameters. The study include (120) blood sample admitted to Mosul Hospital (Central Blood Bank of Mosul for Blood Donation), (60) of them as normal donors and the other (60) received blood to treatment, in order to evaluate the effect of these changes on the recipients after transfusion to avoid transfusion complications as much as possible. There is a highly significant decrease in hemoglobin concentration, packed cell volume (P.C.V. %), and also decrease in total white blood cell (W.B.C.) count and platelets. Key words: Stored blood, blood bank, haematological parameters.